2016
DOI: 10.1002/jsfa.7864
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate pool, sugars and organic acids in black currant (Ribes nigrum L.) berries are strongly influenced by genotype and post‐flowering temperature

Abstract: It is concluded that the post-flowering temperature has marked effects on the concentration of important chemical compounds responsible for taste and nutritional value of black currant berries, whereas photoperiod has no such effect in the studied cultivars. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…The concentration of sugars in these berries was less affected by the variation of radiation. Although with some exceptions, Djordjevic et al () reported a general increase in sugar contents in fruits of black currant ( Ribes nigrum L.) cultivars Ben Sarek, Ben Nevis, Ben Lomond, Ometa, and Čačanska as light intensity increased, which was different from the reports by Woznicki et al () and Zheng, Yang et al (). However, the currant cultivars investigated and the environmental conditions involved in these studies were different from each other.…”
Section: Sugarsmentioning
confidence: 81%
See 2 more Smart Citations
“…The concentration of sugars in these berries was less affected by the variation of radiation. Although with some exceptions, Djordjevic et al () reported a general increase in sugar contents in fruits of black currant ( Ribes nigrum L.) cultivars Ben Sarek, Ben Nevis, Ben Lomond, Ometa, and Čačanska as light intensity increased, which was different from the reports by Woznicki et al () and Zheng, Yang et al (). However, the currant cultivars investigated and the environmental conditions involved in these studies were different from each other.…”
Section: Sugarsmentioning
confidence: 81%
“…mongolica (Zheng, Yang, Trépanier, & Kallio, ) and rhamnoides (Kortesniemi, Sinkkonen, Yang, & Kallio, ). However, such trends were not detected in bilberries (Uleberg et al, ), black currants (Woznicki et al, ; Zheng, Yang, Tuomasjukka, Ou, & Kallio, ) and white currants (Zheng, Kallio et al, ). The concentration of sugars in these berries was less affected by the variation of radiation.…”
Section: Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperatures during the growing season are also associated with the inhibition of various biochemical processes during BC development, which in turn decreases the amount of ascorbic acid produced (Woznicki et al., ). High temperatures (12 to 24 °C) have been shown to reduce the amount of ascorbic acid and the overall sugar content by 27% in BC (Woznicki et al., ). However, higher temperatures do not diminish all desirable properties of BC as citric acid concentrations were increased (Woznicki et al., ).…”
Section: Environmental and Variety Impact On Chemical Compositionmentioning
confidence: 99%
“…High temperatures (12 to 24 °C) have been shown to reduce the amount of ascorbic acid and the overall sugar content by 27% in BC (Woznicki et al., ). However, higher temperatures do not diminish all desirable properties of BC as citric acid concentrations were increased (Woznicki et al., ). It can be concluded from these studies that growing BC plants in colder climates produce berries, which have higher concentrations of beneficial bioactive compounds such as phenolics, which add value to an already high‐value fruit.…”
Section: Environmental and Variety Impact On Chemical Compositionmentioning
confidence: 99%